Caribbean Report 13-06-1995 - Ransome, Debbie (anchor); Richards, Ken (correspondent); Bruney, Mike (interviewee); Alleyne, Brian (interviewee); Douglas, Rosie (interviewee); James, Edison (interviewee); Honychurch, Lennox (interviewee); James, Stanislaus, Sir (interviewee); Ninvalle, Pete (correspondent) (The British Broadcasting Corporation, 1995)
This report looks at the election victory of the United Workers Party (UWP) led by Edison James, has pulled off in Dominica. Dr. Brian Alleyne and Rosie Douglas comment on who will hold the position of Opposition Leader. Prime Minister designate, Edison James talks about the priorities of the in-coming government. Sir Stanislaus James, Governor General of St. Lucia believes cooperation would be increased by political union within the Windward Islands. In St. Lucia, the Opposition boycotts the current budget presentation and the subsequent budget debate. Trinidad and Tobago is to propose the removal of LIAT Chairman William Rapier after he compromised his position. Low key events were held in Guyana on the fifteenth anniversary of the death of Dr. Walter Rodney. In London, the jury has failed to reach verdicts in the case of two officers accused of the manslaughter of Jamaican deportee Joy Gardner.
1. Headlines with Debbie Ransome, anchor (00:00-00:29)
2. In Dominica, a new political party comes into power (00:30-09:44)
3. St. Lucia's Governor-General states that increased cooperation would result from political union (09:45-11:44)
4. St. Lucia's budget debate gets on the way, despite an opposition boycott (11:45-13:36)
Keywords: Dominica -- Politics and government; Politicians -- Dominica; Political parties -- Dominica; Dominica -- Foreign relations; Dominica -- Economic conditions; Political planning -- Dominica; Windward Islands -- Economic integration; Cooperation -- Caribbean Area; Banana trade -- Saint Lucia; Saint Lucia -- Politics and government; Budget -- Saint Lucia; Airlines -- Caribbean Area; Airlines -- Management -- Caribbean Area; Memorials -- Guyana; Assassination -- Guyana; Guyana -- Politics and government; Jury -- Great Britain; Verdicts -- Great Britain; Rodney, Walter -- Assassination